Using Optical Coherence Tomography and Intravascular Ultrasound Imaging to Quantify Coronary Plaque Cap Stress/Strain and Progression: A Follow-Up Study Using 3D Thin-Layer Models - Lv, Rui; Maehara, Akiko; Matsumura, Mitsuaki; Wang, Liang; Zhang, Caining; Huang, Mengde; Guo, Xiaoya; Samady, Habib; Giddens, Don. P.; Zheng, Jie; Mintz, Gary S.; Tang, Dalin (Frontiers in Bioengineering and Biotechnology, 2021)
Accurate plaque cap thickness quantification and cap stress/strain calculations are of fundamental importance for vulnerable plaque research. To overcome uncertainties due to intravascular ultrasound (IVUS) resolution limitation, IVUS and optical coherence tomography (OCT) coronary plaque image data were combined together to obtain accurate and reliable cap thickness data, stress/strain calculations and reliable plaque progression predictions. IVUS, OCT, and angiography baseline and follow-up data were collected from 9 patients (mean age: 69; m: 5) at Cardiovascular Research Foundation with informed consent obtained. IVUS and OCT slices were co-registered and merged to form IVUS+OCT (IO) slices. A total of 114 matched slices (IVUS and OCT, baseline and follow-up) were obtained and 3D thin-layer models were constructed to obtain stress and strain values. A generalized linear mixed model (GLMM) and least squares support vector machines (LSSVM) method were used to predict cap thickness change using nine morphological and mechanical risk factors. Prediction accuracies by all combinations (511) of those predictors with both IVUS and IO data were compared to identify optimal predictor(s) with their best accuracies. For the nine patients, the average of minimum cap thickness from IVUS was 0.17 mm, which was 26.08% lower than that from IO data (average=0.23 mm). Patient variations of the individual errors ranged from ‒58.11% to 20.37%. For maximum cap stress between IO and IVUS, patient variations of the individual errors ranged from ‒30.40% to 46.17%. Patient variations of the individual errors of maximum cap strain values ranged from ‒19.90% to 17.65%. For GLMM method, the optimal combination predictor using IO data had AUC (area under the curve) = 0.926 and highest accuracy = 90.8%, vs. AUC=0.783 and accuracy = 74.6% using IVUS data. For LSSVM method, the best combination predictor using IO data had AUC = 0.838 and accuracy =75.7%, vs. AUC =0.780 and accuracy = 69.6% using IVUS data. This preliminary study demonstrated improved plaque cap progression prediction accuracy using accurate cap thickness data from IO slices and the differences in cap thickness, stress/strain values and prediction results between IVUS and IO data. Large-scale studies are needed to verify our findings.